Turncoats, traitors, and fellow travelers : culture and politics of the early Cold War - Redding, Arthur F., 1964- (University Press of Mississippi, 2008)
The Cold War was unique in the way films, books, television shows, colleges and universities, and practices of everyday life were enlisted to create American political consensus. This coercion fostered a seemingly hegemonic, nationally unified perspective devoted to spreading a capitalist, socially conservative notion of freedom throughout the world to fight Communism. This book traces the historical contours of this manufactured consent by considering the ways in which authors, playwrights, and directors participated in, responded to, and resisted the construction of Cold War discourses.